Pengungkapan Diri Melalui Instagram: Analisis Deskriptif Mengenai Aging Gracefully pada Wanita Paruh Baya - Muhaimin Atmaja Irtonov; Syifa Syarifah Alamiyah (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Self-disclosure through social media instagram has been done by many people including middle-aged women. Self-disclosure is related to the disclosure of feelings, motivations, emotions, and views that middle-aged women have. Middle-aged women have their own concerns about age, where old age causes anxiety and concerns about mental and physical. Until now, a new view related to aging well has emerged, namely Aging Gracefully. The purpose of this study is to find out the self-disclosure carried out by middle-aged women in relation to their Aging Gracefully life. Researchers used descriptive qualitative research methods with data collection techniques through interviews. The results of this study are that there are various descriptions of self-disclosure related to aging gracefully carried out by middle-aged women seen through the lens of the dimensions of self-disclosure, namely the dimensions of amount, valency, accuracy, intention, and intimate. Each person has different levels that are influenced by individual preference factors, communication goals, and trust levels.